Sex Disparity in Stroke Mortality among Adults: A Time Series Analysis in the Greater Vitoria Region, Brazil (2000-2021) - Orivaldo Florencio de Souza; Alexandre Castelo Branco Araújo; Lorenna Baião Vieira; José Alexandre Bachur; Alberto Grover Prado Lopez; Thiago Gomes Gonçalves; Luiz Carlos de Abreu (MDPI AG, 2024)
The disparity between the sexes in stroke mortality has been demonstrated in people from different locations. The objective of this study was to analyze the disparity between sexes in stroke mortality in adults in the metropolitan area of Greater Vitoria between 2000 and 2021. Ecological time series design was conducted with a database of the Brazilian Health System Informatics Department. The annual percentage change and average annual percentage change were calculated through joinpoint regression. Pairwise comparisons using parallelism and coincidence tests were applied to compare temporal trends between men and women. Men had higher mortality rates in most years between 2000 and 2021. In contrast, women had higher proportional mortality values in all years evaluated from 2000 to 2021. The paired comparison revealed a disparity between the sexes in the proportional mortality time series (parallelism test: p = 0.003; coincidence test: p < 0.001). However, the time series of the mortality rates showed no disparity between the sexes (parallelism test: p = 0.114; coincidence test: p = 0.093). From 2000 to 2021, there was a disparity in proportional mortality from stroke between the sexes of the population in the metropolitan area of Greater Vitoria, Brazil. However, the time series of mortality rates between the sexes did not reveal any disparity in the study period.